2016
DOI: 10.1007/s10147-016-1025-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional care of cancer patients: a survey on patients’ needs and medical care in reality

Abstract: With respect to survival and quality of life, increasing the availability and resources for provision of evidence based nutrition information seems mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 16 publications
0
49
0
10
Order By: Relevance
“…Ming-Hua et al (2016) have recently confirmed that high concentrations of IL-1b, IL-6, TNF-α, and LMF are directly involved in cancer cachexia. Indeed, LMF initiates ubiquitin-dependent catabolic pathway and contributes to weight loss during cancer cachexia (Dimitriu et al, 2005) which is, somehow, associated with loss of taste perception as demonstrated by Maschke et al (2017). The inflammatory markers via blood circulation may also exert their action in the brain and modulate the areas involved in the control of feeding behavior including smell and taste perception (Argilés et al, 2014).…”
Section: Cancer: Inflammation and Taste Alterationsmentioning
confidence: 99%
“…Ming-Hua et al (2016) have recently confirmed that high concentrations of IL-1b, IL-6, TNF-α, and LMF are directly involved in cancer cachexia. Indeed, LMF initiates ubiquitin-dependent catabolic pathway and contributes to weight loss during cancer cachexia (Dimitriu et al, 2005) which is, somehow, associated with loss of taste perception as demonstrated by Maschke et al (2017). The inflammatory markers via blood circulation may also exert their action in the brain and modulate the areas involved in the control of feeding behavior including smell and taste perception (Argilés et al, 2014).…”
Section: Cancer: Inflammation and Taste Alterationsmentioning
confidence: 99%
“…The results of the patient survey have been previously reported (Maschke et al, 2017). The results of the patient survey have been previously reported (Maschke et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Data shows that many patients with cancer seek information about nutrition, supplements and cancer diets (Keinki et al, 2016;Maschke et al, 2017;van Veen, Beijer, Adriaans, Vogel-Boezeman, & Kampman, 2015). Yet there is no consistent nutrition care pathway for nutrition management of patients with cancer in Germany.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding and communicating the limitations of naturopathic support therapies when they are initiated late in the course of the cachexia trajectory can reduce unrealistic expectations and decrease burdens on patients and caregivers while educating them on the changes that are occurring. While ongoing and future clinical trials on multimodal treatments for cancer cachexia are much needed and may help us to achieve improvements in outcomes such as quality of life and overall survival for our patients, the synthesis of currently available evidence this article provides serves as a basis and call for routinely employing an integrated approach in an effort to diminish the suffering experienced by those who are at risk for or affected by cancer cachexia (6). Another significant burden in cancer care is the fatigue.…”
Section: Important Issues In Can-cer Patientsmentioning
confidence: 99%